2007
DOI: 10.1007/s10812-007-0063-2
|View full text |Cite
|
Sign up to set email alerts
|

Polarization component method for calculation of the multiple-frequency lasing regime

Abstract: We have shown that the polarization component method can be extended to the case of broadband emission (multiple-frequency approximation) if we make the approximation of slowly varying amplitudes and statistical independence of the polarization components. From the results of numerical modeling for the case of a liquid dye laser, it follows that the multiple-frequency approximation is meaningful to use for analysis of the spectral, polarization, and energy parameters in the region near and below the lasing thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
2
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…In particular, detailed studies of the statistical characteristics of a dye laser based on the PCM have shown [24] that the dispersion in the distribution functions for the individual polarization components can be an order of magnitude greater than that for the total intensity. Something similar is also observed in multimode semiconductor lasers [25], where the dispersion in the distribution functions for the individual modes is considerably greater than that for the total intensity. The difference in the magnitudes of these effects compared to the results obtained using the SFM can now be understood since, in the latter case, there are only two independent polarization modes.…”
supporting
confidence: 68%
“…In particular, detailed studies of the statistical characteristics of a dye laser based on the PCM have shown [24] that the dispersion in the distribution functions for the individual polarization components can be an order of magnitude greater than that for the total intensity. Something similar is also observed in multimode semiconductor lasers [25], where the dispersion in the distribution functions for the individual modes is considerably greater than that for the total intensity. The difference in the magnitudes of these effects compared to the results obtained using the SFM can now be understood since, in the latter case, there are only two independent polarization modes.…”
supporting
confidence: 68%
“…This approach (the polarization component method) turned out to be especially effective in the region near the lasing threshold, where the standard polarization mode method is not generally workable [21,22]. Later it was shown [23] that the polarization component method can be used for describing the formation of polarized radiation in semiconductor lasers. Thus, it seems fully logical to use the polarization component method for describing polarization switching effects in semiconductor lasers, since, in the polarization switching region, owing to the equality of the difference in the gain and loss coefficients for waves with different polarizations, it is hardly possible to justify the concept of a "polarization mode" because of its instability.…”
mentioning
confidence: 99%
“…The polarization component method is discussed in detail elsewhere [21][22][23], so here we shall only discuss some key points to be used in constructing the theoretical model. In the polarization component method the field E(z, t) of a plane wave propagating along the z axis is written in the form of a superposition of polarization components:…”
mentioning
confidence: 99%